Peningkatan Psychological Well-Being pada Lanjut Usia di UPT Tresna Werdha Kabupaten Jember - Hidayati, Nurul Aini; Choliq, Abdul (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2023)
Old age is a phase that generally begins around the age of 60, marked by physical changes and often accompanied by a decline in memory. This issue will affect the lives of the elderly throughout their lifetime, leading to feelings of uselessness, lack of attention, a sense of isolation, and potentially becoming a burden to those around them. Based on field findings, 1 in 5 seniors requires periodic psychological improvement. Therefore, the Tresna Werdha Social Service in Jember Regency collaborates with psychiatrists. Seniors in need of psychological improvement receive continuous care because they may still struggle to accept their current condition.  Psychological well-being is a form of individual psychological health based on positive psychological functions. This research uses a qualitative method with a descriptive approach, presenting and analyzing research materials obtained from interviews, observations, and documentation. The research findings indicate:1. Psychological Well-Being in the elderly at the Tresna Werdha Social Service (PSTW) in Jember Regency has been addressed through planned and organized activities to improve their psychological well-being. 2. Challenges in enhancing the psychological well-being of the elderly at the Tresna Werdha Home in Jember Regency include the seniors' health, limitations of caregivers, the psychological condition of the elderly, and the decline in physical/motor skills of the elderly